1973
DOI: 10.1007/bf01609537
|View full text |Cite
|
Sign up to set email alerts
|

Zonation of algae and sessile invertebrates in the Glénan Archipelago. Biologic definition of bathymetric zones

Abstract: Zonation of algae and sessile invertebrates in the Gl6nan Archipelago. Biologic definition of bathymetric zones. The GI6nan Archipelago was investigated, from the surface to a depth of 60 m, by SCUBA diving. Four distinct communities ("peuptements") have been determined that fit into the system of zonation defined by the Genoa Symposium (1957). The results are compared with observations made in the English Channel (CA~IOCH 1968) and in the Atlantic Ocean (GLEMAI~C 1971). Since illumination depends upon the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…A certain likeness is also found with the 'phases d e recruternent'and 'd'installation' described by Castric Fey (1974) and Castric (1977) for a community in the English Channel, where in 11 mo about 75 % of the species growing on the surrounding rocks settled on the artificial substrates.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A certain likeness is also found with the 'phases d e recruternent'and 'd'installation' described by Castric Fey (1974) and Castric (1977) for a community in the English Channel, where in 11 mo about 75 % of the species growing on the surrounding rocks settled on the artificial substrates.…”
Section: Discussionsupporting
confidence: 70%
“…The evolution of benthic populations on natural and artificial substrates was divided up into well-defined stages by determining the main categories of environmental factors governing the development process while looking for signs that the final stage or climax has been reached (Simon Papyn 1965, Bellan Santini 1970, Huve 1970, Castric Fey 1974, Castric 1977. The importance of some physical and biotic factors in controlling community development has been underlined by research in caves (Vacelet 1976, Harmelin 1980, 1983, a relatively simple environment due to the predominating influence of a comparatively small number of environmental factors and their stability.…”
Section: Introductionmentioning
confidence: 99%
“…12) 11 Jerlov water type calculated from data of authors 12 Boutler et al (1974) 13 depth below E.L.W.S. 14 measured by thermopile is Castric-Fey et al (1973) 16 Descatoire et al (1969) 17 young plants 18 Neushul (1971) 19 below canopy of…”
Section: Discussionmentioning
confidence: 99%
“…near Helgoland) has been recognized by more and more workers and regarded as the uppermost part of the sublittoral region (see Table 4). Laminaria digitata is a typical inhabitant of the infralittoral fringe (Castric-Fey et al, 1973) and is specially adapted for this habitat by its flexible stipe. Kain (1976) observed that this species, together with others, colonised cleared areas well below its usual zone, but was outcompeted after 4 years by L. hyperborea which finally overshadowed the other species due to its possession…”
Section: Macrocystis Pyriferamentioning
confidence: 99%
“…On most European coasts Laminaria digitata inhabits the uppermost part of the sublittoral region, whereas L. hyperborea and (locally) L. saccharina dominate the middle and deeper parts of the kelp zone (Kain, 1962;Castric-Fey et al, 1973; Gayral & Cosson, 1973). L. digitata is well adapted for colonizing the upper sublittoral region, e.g.…”
Section: Introductionmentioning
confidence: 99%